Penerapan Model CIRC Berbantuan Media Flipping Book pada Materi Getaran, Gelombang, dan Bunyi Untuk Meningkatkan Hasil Belajar IPA di SMP - Ramsyiah Ramsyiah; Hafnati Rahmatan; Muhammad Syukri; Yusrizal Yusrizal; Elisa Elisa (Postgraduate, University of Mataram, 2023)
21st-century learning requires students to be equipped to process and use the information activities such as applying the CIRC learning model assisted by flipping book media. This study aims to determine the application of the CIRC learning model assisted by flipping book media to improve science learning outcomes. The research design used was the pretest-posttest control group. The population of this study was eighth-grade students at SMPN 1 and SMPN 2 Simeulue Timur because, based on data and observations, science learning outcomes were still low and taught using a teacher-centered model. The sample was determined using the purposing technique Sampling, which resulted in 108 students divided into two classes. The results showed that the N-Gain value of the experimental class was 56.96 and the control class was 28,04 and thit> ttab (9.42 > 1.98), indicating differences in the increase in cognitive learning outcomes of the two types of classes.